2019
DOI: 10.1177/2325967119885370
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic Intra-articular Changes of the Knee in Adult Professional Soccer Players

Abstract: Background: Currently, there are few data on the association between participation in soccer and the condition of the knee joints in adult professional players. Hypothesis: A high percentage of professional soccer players will have asymptomatic intra-articular changes of the knee. Study Design: Cross-sectional study; Level of evidence, 3. Methods: The condition of the intra-articular structures (osteophytes, cartilage, and menisci) in 94 knee joints of 47 adult professional soccer players (mean ± SD age, 25.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Two, the imaging appearance of the articular cartilage of the foot and ankle joints was assessed with a modified Noyes and Stabler scale, 23 as used in our previous work 6 and validated for our setting: Grade 0: normal thickness and signal; Grade 1: normal thickness with an altered signal; Grade 2: superficial partial-thickness cartilage defect (<50% of the total cartilage thickness affected); Grade 3: deep partial-thickness cartilage defect (>50% of the total cartilage thickness affected); Grade 4: full-thickness chondral defect with exposure of subchondral bone …”
Section: Methodsmentioning
confidence: 99%
“…Two, the imaging appearance of the articular cartilage of the foot and ankle joints was assessed with a modified Noyes and Stabler scale, 23 as used in our previous work 6 and validated for our setting: Grade 0: normal thickness and signal; Grade 1: normal thickness with an altered signal; Grade 2: superficial partial-thickness cartilage defect (<50% of the total cartilage thickness affected); Grade 3: deep partial-thickness cartilage defect (>50% of the total cartilage thickness affected); Grade 4: full-thickness chondral defect with exposure of subchondral bone …”
Section: Methodsmentioning
confidence: 99%
“…13-18 In addition, previous studies focusing on soccer players showed good results with various cartilage repair techniques. 1-3 In this study the most common surgical treatment across all FMCE in the past 10 years was bone marrow stimulation/microfracture, followed by debridement. Twelve centers (80%) from around the world reported on performing bone marrow stimulation/microfracture in 1% to 80% of their surgical cartilage cases.…”
Section: Discussionmentioning
confidence: 82%
“…Soccer players have an overall high prevalence of knee articular cartilage lesions (from 36% in asymptomatic players and up to 98% in symptomatic). 1-4 This high prevalence, which includes different lesion grades and locations, is attributed to the high prevalence of anterior cruciate ligament (ACL) and meniscal injuries, as well as the inherent risks of the game. 1,2,5 The symptomatic articular cartilage lesions may lead to reduced athletic performance, an early career ending, and also early onset of knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…They identified meniscal lesions in 97.8% of joints and cartilage lesions in both knees in 97.9% of soccer players. 8 The purpose of our retrospective review is to investigate the impact of medial meniscus repair on player performances and longevity in Major League Soccer (MLS), the top tier professional soccer league in the United States of America. We hypothesize that players will have reduced performance metrics after medial meniscus repair.…”
Section: Introductionmentioning
confidence: 99%